Sedimentological and Geochemical Analysis of the Upper Paleozoic Sedimentary Sequences in Kinta Valley, Peninsular Malaysia - Chow Weng Sum, Chow (2012)
the palaeozoic sequence stratigraphic position and geological age of the Kinta Valley limestone and associated clastics are not well understood. Subjection to diagenetic and metamorphic alterations increases the difficulties in the application of sedimentological study. Geochemical results show temporal and spatial variation from north to southeast of the Kinta valley limestone sequences. Mainly it shows a low MgO (2.38 wt %) at the northern (Khantan) and relatively higher (7.61 wt %) in the southeast of Kinta Valley (Kampar). It also characterized by having lower trivalent oxides of Fe and Al in the older outcrops than that of the younger carbonate outcrops. Sr elemental variation of the analysed samples also followed the same trend but in a decreasing order towards the southeast. The implication of this compositional variation might be linked to fluid-rock interaction during the metamorphism episode or can be considered as a reflection of contemporaneous palaeo-sea water composition. Petrographic analyses of 33 thin sections showed that the limestone is crystallized to form marble and/or affected by diagenesis. Thus, sedimentological investigation of the Kinta Valley sequences needs to be integrated with geochemical studies to have a better understanding of the lithofacies, its regional stratigraphic position and possibly to determine the geological age of the non-fossiliferous intervals. In this contribution, geochemical analysis integrated with sedimentological and paleontological studies are presented.